2002
DOI: 10.1046/j.1432-1033.2002.02779.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of substrate specificity of human aromatase by site directed mutagenesis

Abstract: Human aromatase is responsible for estrogen biosynthesis and is implicated, in particular, in reproduction and estrogen-dependent tumor proliferation. The molecular structure model is largely derived from the X-ray structure of bacterial cytochromes sharing only 15-20% identities with hP-450arom. In the present study, site directed mutagenesis experiments were performed to examine the role of K119, C124, I125, K130, E302, F320, D309, H475, D476, S470, I471 and I474 of aromatase in catalysis and for substrate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 61 publications
7
29
0
Order By: Relevance
“…Our results, in combination with those of Haiman et al (17), suggest that this polymorphism or one in linkage disequilibrium with it may alter the binding affinity of the CYP19 protein (aromatase) to testosterone and androstenedione versus 16␣-hydroxyandrostenedione. Data suggest that 16␣-hydroxyandrostenedione has a separate binding site from that of testosterone and androstenedione but that each hormone inhibits the aromatization of the others (40,41). Thus, individuals with the 7r(Ϫ3) allele may produce proteins with a higher binding affinity for 16␣-hydroxyandrostenedione, which would inhibit the binding of androstenedione and testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, in combination with those of Haiman et al (17), suggest that this polymorphism or one in linkage disequilibrium with it may alter the binding affinity of the CYP19 protein (aromatase) to testosterone and androstenedione versus 16␣-hydroxyandrostenedione. Data suggest that 16␣-hydroxyandrostenedione has a separate binding site from that of testosterone and androstenedione but that each hormone inhibits the aromatization of the others (40,41). Thus, individuals with the 7r(Ϫ3) allele may produce proteins with a higher binding affinity for 16␣-hydroxyandrostenedione, which would inhibit the binding of androstenedione and testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the D309A mutant which induced activity loss with androstenedione as well as testosterone, exhibited activity with nor-testosterone. In contrast, the mutant E302A was found to be inactive with all the three substrates [10]. This suggests that E302 has an important part to play in the enzymatic mechanism involving both androgens as well as nor-androgens.…”
Section: Introductionmentioning
confidence: 90%
“…Earlier site directed mutagenesis studies on D309 of human aromatase implied the probable role of this aspartate in decarboxylation of androstenedione or testosterone and attracting a proton at C2 of the steroids during aromatization [7][8][9]. This process is assumed to be assisted by basic residues H475 and K473 present in proximity to C3 [10]. Previous site directed mutagenesis studies suggested that the repulsive force between D476 and E309 may be important for efficient aromatization of C19-androgens.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatase activity 'in cell' was evaluated 48 h post-transfection. Transfection efficiency was evaluated by ELISA of the wild-type and several mutated proteins without showing differences in recombinant aromatase expressions (16).…”
Section: E293 Cell Culture and Transient Transfection Assaymentioning
confidence: 99%